The impact of tourism sector towards economy growth in Malaysia / Ahmad Kamil Hasan Abdul Wahab - Abdul Wahab, Ahmad Kamil Hasan (Faculty of Business and Management, 2015)
This paper aim at finding out the impact of tourism sector towards economic growth in Malaysia which the economic growth is monitor based on the gross domestic product (GDP). The variables are considered are tourist arrivals (TA), job employment (JE), tourist receipts (TR), and exchange rate (EA). This study required 30 years data for each of the variable from 1984 until 2013. Methodology used for this study is by using Multiple Linear Regression with series data. Thereafter, econometric test are to be conducted to observe the relationship of the independent variables with economy growth which is GDP. Interactive software package E-view would be used for testing and analyzing the data collected. The study is attempt to investigate there is a significant relationship between the independent variables with the GDP and which variables contributes most to the economic growth. Findings from previous study mostly shows that tourist arrivals, job employment and tourist receipts has a significant role in the determination of economic growth. As guidance to the past research that have been done, this study will examine the relationship between impact of tourism sector and economic growth.